Pendekatan Strategi dalam Promosi dan Pengelolaan Usaha UMKM untuk Meningkatkan Daya Saing Warung Oma Abang di Kelurahan Labuh Baru Timur Kecamatan Payung Sekaki Pekanbaru - Nur Fitriana; Dinda Ramadhani; Mazaya Dhia Hanifa; Remia Siahaan; Della Pratiwi Gercya; Najla Zahrani Raudatunisha (LPPI UMN AL WASHLIYAH, 2025)
Micro, Small, and Medium Enterprises (MSMEs) constitute a significant segment of the economy; however, many entities in this sector continue to face challenges related to business management and marketing strategies. Warung Oma Abang serves as an illustration of a culinary MSME that has faced a myriad of issues, including no registration on Google Maps, inadequate promotional activities, lack of a menu catalog, reliance on manual transaction documentation, and unavailability of digital payment options such as QRIS. The primary objective of this initiative was to improve the visibility and operational efficacy of Warung Oma Abang through comprehensive mentoring. The methodology used included problem identification, formulation of strategic solutions, and direct implementation in a practical setting. The mentoring effort involved registration on Google Maps, a menu catalog, creating promotional banners, managing an Instagram account as a platform for promotions, shifting financial records to a simplified digital framework, and facilitating the QRIS registration process. The results of this initiative showed increased online visibility, increased customer accessibility to the menu, improved aesthetic appeal, and increased efficiency in financial documentation and payment modalities. In conclusion, mentoring that uses a practical and focused methodology can significantly assist MSMEs in overcoming operational challenges and expanding their customer reach.